Some blood parameters in healthy kangal dogs - Leyla Kalaycıoğlu; Mehmet Nizarnoğlu; Vahdettin Altunok (Eurasian Journal of Veterinary Sciences)
In this study, 10 healthy Kangal dogs, bred Faculty of Veterinary Medicine, Selçuk University were used. Dogs were either sex and were 3 months to 3 years old. Serum concentrations of total protein,albumin, sodium, potassium and activity of serum aspartate aminotransferase were measured. The mean values for these paramaters were 5.34±1 .38 g/dl, 3.42±0.64 g/dl, 130.2±14.63 mM o lll, 4.91±0.81 mM o llL and 38.1 ±9.05 U/L respectively.